49x+1=48x+3

Simple and best practice solution for 49x+1=48x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 49x+1=48x+3 equation:


Simplifying
49x + 1 = 48x + 3

Reorder the terms:
1 + 49x = 48x + 3

Reorder the terms:
1 + 49x = 3 + 48x

Solving
1 + 49x = 3 + 48x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-48x' to each side of the equation.
1 + 49x + -48x = 3 + 48x + -48x

Combine like terms: 49x + -48x = 1x
1 + 1x = 3 + 48x + -48x

Combine like terms: 48x + -48x = 0
1 + 1x = 3 + 0
1 + 1x = 3

Add '-1' to each side of the equation.
1 + -1 + 1x = 3 + -1

Combine like terms: 1 + -1 = 0
0 + 1x = 3 + -1
1x = 3 + -1

Combine like terms: 3 + -1 = 2
1x = 2

Divide each side by '1'.
x = 2

Simplifying
x = 2

See similar equations:

| 2.86-21.1= | | (-18)=5x-8 | | 2r-r=9 | | =-3/7x-1/7 | | 5(0)=15+3y | | x+6=-5(x+6) | | 9a-18= | | 4*y-8=3*y+12 | | 10b-2=2b+14 | | 5+2m=6m+11 | | (10x+16)+54=90 | | 2(3x+5)+3=4x+7 | | 16000=650x-24000 | | 1y+2y= | | -7(4-5x)=-273 | | Y+20=4x | | -5(3-3x)+2x=-66 | | 3x+2(x+17)=149 | | -45=5s+20 | | 3(x-5)+1=4 | | -6a-6=-30 | | 40x^2-13x=3x^2+34x^2+5x | | 57+14x^2-12-13x-8x^2=5x+45 | | 23x-2=22x+1 | | 45x+60x*185y=10500 | | 3.6=0.6 | | 2-3*y=7*y+12 | | 3(-4+5g)=9g | | 0.66(2x-5)=0.75(x-2) | | 70=5g+3m | | 2a+5-5a= | | -72+9s=-81 |

Equations solver categories